A low-sensitivity energetic composite material and a solvent-free preparation method thereof
Patent Information
- Application Number
- CN202611091120.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-27
AI Technical Summary
目前,该技术的主要问题体现在有机溶剂大多具有严重的生物毒性,并且危害环境,致使后续进行无害处理成本高
[0016]有益效果:与现有技术相比,本发明具有如下显著优点:本发明制备方法全过程无有机溶剂参与,凭借虫胶、HTPB自身的黏度和高氯酸铵颗粒间的摩擦实现钝感材料的均匀包覆,制备工艺简单,工序少(无常规驱溶干燥过程),易于控制和放大,效率高。
Smart Images

Figure CN122977912A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a low-sensitivity energetic composite material and its solvent-free preparation method, belonging to the field of energetic materials. Background Technology
[0002] In the field of energetic materials, methods such as physical coating, chemical eutectic, or the addition of desensitizing agents are often used to reduce the sensitivity of insensitive energetic composites to external mechanical stimuli (such as impact and friction) and thermal stimuli, thereby significantly improving their inherent safety during production, storage, and transportation. Insensitive energetic composites typically use high-energy oxidants or explosives as the core, with a surface modified with a desensitizing layer to achieve a balance between high energy and low sensitivity.
[0003] Ammonium perchlorate (NH4ClO4), as a strong oxidizing agent, possesses advantages such as high density, high oxygen content, and good thermal and chemical stability, occupying an extremely important position in solid propellants. Typically, ammonium perchlorate is one of the main components of solid propellants, accounting for 60%-80% of the total weight. However, ammonium perchlorate is classified as a Class 1.1 explosive, and its high mechanical sensitivity reduces the safety performance of weapon propulsion systems during production and use.
[0004] To address the high mechanosensitivity of ammonium perchlorate, current methods employ desensitizing materials for coating. However, these methods almost exclusively utilize wet coating processes, where the coating material is dissolved in an organic solvent and then deposited onto the ammonium perchlorate surface due to differences in solubility. The main problem with this technology is that most organic solvents are highly toxic to organisms and environmentally harmful, leading to high costs associated with subsequent harmless treatment. Summary of the Invention
[0005] Purpose of the invention: The purpose of this invention is to provide a low-sensitivity energetic composite material that is non-biotoxic; another purpose of this invention is to provide a solvent-free preparation method for the low-sensitivity energetic composite material.
[0006] Technical solution: The low-sensitivity energetic composite material of the present invention includes ammonium perchlorate and a coating material coating the outer layer of ammonium perchlorate. The coating material includes a desensitizing material, shellac and hydroxyl-terminated polybutadiene; the desensitizing material is paraffin or carbon material.
[0007] The coating material, by mass percentage, comprises 40%-50% of a desensitizing material, 40%-48% of shellac, and 10%-12% of hydroxyl-terminated polybutadiene.
[0008] Preferably, the mass ratio of the coating material to ammonium perchlorate is not less than 1:60. More preferably, the mass ratio of the coating material to ammonium perchlorate is 1:50-60.
[0009] Preferably, the insensitive material is selected from 70# paraffin wax, 58# paraffin wax, ceresin wax, beeswax, graphite powder, graphene oxide, and fluorinated graphene.
[0010] On the other hand, the present invention provides a solvent-free preparation method for the above-mentioned low-sensitivity energetic composite material, comprising the following steps:
[0011] Step 1: Pretreatment of the coating material: After the insensitive material, shellac and hydroxyl-terminated polybutadiene are mixed evenly, they are subjected to calendering and extrusion to obtain the coating material;
[0012] Step 2: Solvent-free coating: Ammonium perchlorate and coating material are added alternately to the mixer. The specific order of addition is as follows: first add a layer of ammonium perchlorate, then add half of the coating material, then add the remaining ammonium perchlorate, and finally add the other half of the coating material. After the addition is completed, the mixing tank is sealed and vacuumed. The reaction is carried out under heating and stirring conditions. After the reaction is completed, the material is discharged to obtain the low-sensitivity energetic composite material.
[0013] This invention employs a solvent-free coating process to coat ammonium perchlorate with specific desensitizing materials. It mainly involves two basic steps: pretreatment of the coating material and solvent-free coating. The resulting product has a uniform particle size distribution, good desensitization effect, and the preparation process is simple, pollution-free, easy to control and scale up, and highly efficient.
[0014] In step one, the mixing process is performed using a two-roll mill, and the calendering and extrusion process is performed using a rod extruder. Specifically, the insensitive material, shellac, and hydroxyl-terminated polybutadiene are repeatedly milled in the two-roll mill until they are uniformly mixed.
[0015] In step two, the specific process parameters for the reaction under heating and stirring conditions are as follows: stirring speed controlled at 5~20 rpm, and heating temperature at 0~100℃. Preferably, in step two, the heating time is 40-180 min.
[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: The preparation method of the present invention does not involve organic solvents throughout the entire process. It achieves uniform coating of insensitive materials by relying on the viscosity of shellac and HTPB and the friction between ammonium perchlorate particles. The preparation process is simple, with few steps (no conventional solvent removal and drying process), easy to control and scale up, and highly efficient. Attached Figure Description
[0017] Figure 1This is a SEM image of ammonium perchlorate, the raw material of this invention.
[0018] Figure 2 This is a SEM image of the low-sensitivity energetic composite material of Example 1 of the present invention.
[0019] Figure 3 This is a SEM image of the low-sensitivity energetic composite material of Example 2 of the present invention.
[0020] Figure 4 This is a SEM image of the low-sensitivity energetic composite material of Example 3 of the present invention.
[0021] Figure 5 This is a SEM image of the low-sensitivity energetic composite material of Example 4 of the present invention.
[0022] Figure 6 This is a SEM image of the ammonium perchlorate composite material of Comparative Example 1 of the present invention.
[0023] Figure 7 This refers to the pre-treated coating material used in Embodiment 1 of the present invention.
[0024] Figure 8 The results are from the sensitivity test of this invention. Detailed Implementation
[0025] The technical solution of the present invention will be further described below with reference to the accompanying drawings.
[0026] Example 1
[0027] This embodiment provides a low-sensitivity energetic composite material, wherein the mass ratio of ammonium perchlorate to the coating material is 50:1; and the coating material is composed of 50% paraffin, 40% shellac and 10% HTPB by mass percentage.
[0028] The preparation method of the above-mentioned low-sensitivity energetic composite material is as follows: Weigh 30g of 70# paraffin powder and 24g of shellac, mix them simply, and then place them in a two-roll mill for calendering and mixing more than 10 times. During the process, add 6g of type I HTPB. Then, use a screw extruder to expand the specific surface area of the coating material for later use. Weigh 3000g of ammonium perchlorate, first place 1500g at the bottom of the material cylinder of a planetary mixer, add 30g of coating material, and then add the remaining ammonium perchlorate and 30g of coating material in sequence. Raise the material cylinder and seal it, evacuate to below -0.07MPa, start the stirring and heating program, turn the speed to 15rpm, raise the temperature to 65℃ and stir for 1 hour. Stop stirring, take out the material and sieve it through an 8-mesh sieve to obtain the low-sensitivity energetic composite material.
[0029] Example 2
[0030] This embodiment provides a low-sensitivity energetic composite material, wherein the mass ratio of ammonium perchlorate to coating material is 50:1; and the coating material is composed of 50% graphite powder, 40% shellac and 10% HTPB by mass percentage.
[0031] The preparation method of the above-mentioned low-sensitivity energetic composite material is as follows: 30g of graphite powder and 24g of shellac are weighed and simply mixed. The mixture is then placed in an open mill and calendered more than 10 times, with 6g of type I HTPB added during the process. The coating material is then subjected to surface area expansion treatment using a screw extruder. 3000g of ammonium perchlorate is weighed, and 1500g is placed at the bottom of the planetary mixer's feed cylinder. 30g of the coating material is added, followed by the remaining ammonium perchlorate and another 30g of coating material. The feed cylinder is raised and sealed, and a vacuum is drawn to below -0.07MPa. The stirring and heating program is started at 15rpm, and the temperature is raised to 65℃. Stirring is then carried out for 1 hour, after which stirring is stopped. The material is then sieved through an 8-mesh sieve to obtain the low-sensitivity energetic composite material.
[0032] Example 3
[0033] This embodiment provides a low-sensitivity energetic composite material, wherein the mass ratio of ammonium perchlorate to the coating material is 50:1; and the coating material is composed of 50% paraffin, 40% shellac and 10% HTPB by mass percentage.
[0034] The preparation method of the above-mentioned low-sensitivity energetic composite material is as follows: 30g of 70# paraffin powder and 24g of shellac are weighed and simply mixed. The mixture is then placed in an open mill and calendered more than 10 times, with 6g of type 1 HTPB added during the process. The coating material is then subjected to surface area expansion treatment using a screw extruder. 3000g of ammonium perchlorate is weighed, and 1500g is placed at the bottom of the planetary mixer's feed cylinder. 30g of the coating material is added, followed by the remaining ammonium perchlorate and another 30g of coating material. The feed cylinder is raised and sealed, and a vacuum is drawn to below -0.07MPa. The stirring and heating program is started at 15rpm, and the temperature is raised to 65℃. Stirring is then carried out for 2 hours. Stirring is stopped, and the material is sieved through an 8-mesh sieve to obtain the low-sensitivity energetic composite material.
[0035] Depend on Figure 4 It can be seen that as the mixing time increases, the materials stick together severely.
[0036] Example 4
[0037] This embodiment provides a low-sensitivity energetic composite material, wherein the mass ratio of ammonium perchlorate to coating material is 60:1; and the coating material is composed of 40% paraffin, 48% shellac and 12% HTPB by mass percentage.
[0038] The preparation method of the above-mentioned low-sensitivity energetic composite material is as follows: 20g of 70# paraffin powder and 24g of shellac are weighed and simply mixed. The mixture is then placed in an open mill and calendered more than 10 times, with 6g of type 1 HTPB added during the process. The coating material is then subjected to surface area expansion treatment using a screw extruder. 3000g of ammonium perchlorate is weighed, and 1500g is placed at the bottom of the planetary mixer's feed cylinder. 25g of the coating material is added, followed by the remaining ammonium perchlorate and another 25g of coating material. The feed cylinder is raised and sealed, and a vacuum is drawn to below -0.07MPa. The stirring and heating program is started at 15rpm, and the temperature is raised to 65℃. Stirring is then carried out for 1 hour, after which stirring is stopped. The material is then sieved through an 8-mesh sieve to obtain the low-sensitivity energetic composite material.
[0039] Example 5
[0040] This embodiment provides a low-sensitivity energetic composite material, wherein the mass ratio of ammonium perchlorate to the coating material is 50:1; and the coating material is composed of 50% paraffin, 40% shellac and 10% HTPB by mass percentage.
[0041] The preparation method of the above-mentioned low-sensitivity energetic composite material is as follows: 30g of 70# paraffin powder and 24g of shellac are weighed and simply mixed. The mixture is then placed in an open mill and calendered more than 10 times. During this process, 6g of type I HTPB is added. The coating material is then processed through a screw extruder to increase its specific surface area. 3000g of ammonium perchlorate is weighed. 1500g is placed at the bottom of the planetary mixer's feed cylinder, followed by 30g of the coating material. Then, the remaining ammonium perchlorate and another 30g of coating material are added sequentially. The feed cylinder is raised and sealed, and a vacuum is drawn to below -0.07MPa. The stirring and heating program is started at 20rpm. After heating to 60℃, the mixture is stirred for 40 minutes. Stirring is then stopped, and the material is sieved through an 8-mesh sieve to obtain the low-sensitivity energetic composite material.
[0042] Example 6
[0043] This embodiment provides a low-sensitivity energetic composite material, wherein the mass ratio of ammonium perchlorate to coating material is 60:1; and the coating material is composed of 40% paraffin, 48% shellac and 12% HTPB by mass percentage.
[0044] The preparation method of the above-mentioned low-sensitivity energetic composite material is as follows: 20g of 70# paraffin powder and 24g of shellac are weighed and simply mixed. The mixture is then placed in an open mill and calendered more than 10 times. During this process, 6g of type 1 HTPB is added. The coating material is then processed through a screw extruder to increase its specific surface area. 3000g of ammonium perchlorate is weighed. 1500g is placed at the bottom of the planetary mixer's feed cylinder, followed by 25g of the coating material. Then, the remaining ammonium perchlorate and another 25g of coating material are added sequentially. The feed cylinder is raised and sealed, and a vacuum is drawn to below -0.07MPa. The stirring and heating program is started at 5rpm. After heating to 90℃, the mixture is stirred for 180 minutes. Stirring is then stopped, and the material is sieved through an 8-mesh sieve to obtain the low-sensitivity energetic composite material.
[0045] Comparative Example 1:
[0046] This comparative example provides an ammonium perchlorate composite material, wherein the mass ratio of ammonium perchlorate to coating material is 50:1; the coating material, by mass percentage, consists of 50% paraffin wax, 40% shellac, 10% HTPB and toluene solvent.
[0047] The preparation method of the above-mentioned ammonium perchlorate composite material is as follows: Weigh 30g of 70# paraffin powder and 6g of type 1 HTPB, dissolve them in 400mL of toluene, weigh 24g of shellac, and dissolve it in 400mL of anhydrous ethanol. Weigh 3000g of ammonium perchlorate and place it in a double cone mixer. First, pour in the toluene solution, then slowly pour in the ethanol solution. Close the feed port of the mixer, evacuate to -0.07MPa, start mixing, and the mixing time is 2 hours.
[0048] Discharge the material and place it in a tray. Put the tray in a vacuum drying oven, turn on the oven, and dissolve for 4 hours. Cool to room temperature and sieve using an 8-mesh sieve.
[0049] To evaluate the mechanical sensitivity of the raw material ammonium perchlorate (AP) and the low-sensitivity energetic composite materials prepared in Examples 1, 2, and Comparative Example 1, impact sensitivity and friction sensitivity tests were conducted according to the explosion probability method specified in GJB 772B "Test Methods for Gunpowder". The impact sensitivity test was conducted using a vertical falling weight apparatus at a falling weight mass of 10 kg and a falling height of 25 cm. The probability (%) of the sample burning or exploding after impact was used to evaluate the impact resistance performance; a lower probability indicates higher safety. The friction sensitivity test was conducted using a pendulum friction apparatus at a gauge pressure of 3.92 MPa and a pendulum angle of 90°. The probability (%) of the sample burning or exploding after friction was used to evaluate the risk of friction-induced accidents; a lower probability indicates better safety during processing and use.
[0050] like Figure 8The sensitivity test results shown indicate that the low-sensitivity energetic composite materials prepared in Examples 1 and 2 exhibit excellent mechanical sensitivity, significantly lower than that of the raw material ammonium perchlorate and Comparative Example 1, demonstrating better safety performance.
Claims
1. A low-sensitivity energetic composite material, characterized in that, It includes ammonium perchlorate and a coating material covering the outer layer of ammonium perchlorate, wherein the coating material includes a desensitizing material, shellac, and hydroxyl-terminated polybutadiene; the desensitizing material is paraffin or carbon material.
2. The low-sensitivity energetic composite material according to claim 1, characterized in that, The coating material comprises, by weight percentage, 40%-50% of a desensitizing material, 40%-48% of shellac, and 10%-12% of hydroxyl-terminated polybutadiene.
3. The low-sensitivity energetic composite material according to claim 1, characterized in that, The mass ratio of the coating material to ammonium perchlorate is not less than 1:
60.
4. The low-sensitivity energetic composite material according to claim 3, characterized in that, The mass ratio of the coating material to ammonium perchlorate is 1:50-60.
5. The low-sensitivity energetic composite material according to claim 1, characterized in that, The insensitive material is selected from 70# paraffin wax, 58# paraffin wax, ceresin wax, beeswax, graphite powder, graphene oxide, and fluorinated graphene.
6. A solvent-free preparation method for a low-sensitivity energetic composite material according to any one of claims 1-5, characterized in that, Includes the following steps: Step 1: After uniformly mixing the insensitive material, shellac, and hydroxyl-terminated polybutadiene, the mixture is subjected to calendering and extrusion to obtain the coating material; Step 2: Add ammonium perchlorate and coating material alternately to the mixer. The specific order of addition is as follows: first add a layer of ammonium perchlorate, then add half of the coating material, then add the remaining ammonium perchlorate, and finally add the other half of the coating material. After the addition is completed, seal the mixing tank and evacuate it. The reaction is carried out under heating and stirring conditions. After the reaction is completed, the material is discharged to obtain the low-sensitivity energetic composite material.
7. The solvent-free preparation method according to claim 6, characterized in that, In step one, the apparatus used for uniform mixing is an open mill, and the apparatus used for calendering and extrusion is a rod extruder.
8. The solvent-free preparation method according to claim 6, characterized in that, In step one, the insensitive material, shellac, and hydroxyl-terminated polybutadiene are placed in a two-roll mill and repeatedly crushed until they are evenly mixed.
9. The solvent-free preparation method according to claim 6, characterized in that, In step two, the specific process parameters for the reaction under heating and stirring conditions are as follows: the stirring speed is controlled at 5~20 rpm, and the heating temperature is 60~90℃.
10. The solvent-free preparation method according to claim 9, characterized in that, In step two, the heating time is 40-180 minutes.